The Double-Edged Impact of Artificial Intelligence on Students’ Critical Thinking Skills in Indonesia: A Systematic Literature Review - Putu Andre Wiranatha; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (Journal of Education and Teaching Learning, 2026)
Nowadays Artificial Intelligence (AI) has become an inseparable part of the world of education. Therefore, it’s important to examine the impact on AI on the critical thinking skill. This study aims to examine the positive and negative impact of AI on students critical thinking in Indonesia. This critical thinking aspect including interpretation, analysis, evaluation, inference, synthesize explanation, and self-regulation. Using systematic literature review method with PRISMA model. There are 136 studies as a database and 17 has been reviewed. The results of this study found that AI both have positive and negative impact on students critical thinking skills. But negatively impacts almost all dimensions of critical thinking, especially Interpretation, analysis, evaluation, inference, self-regulation, and explanation. For future research, it is recommended that researchers explore the long-term impact of AI use on students' critical thinking skills.